2016
DOI: 10.1002/2015jd024389
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly evolving ultrafine and fine mode biomass smoke physical properties: Comparing laboratory and field results

Abstract: Combining field and laboratory results, we present biomass smoke physical properties. We report sub-0.56 μm diameter (D p ) particle sizing (fast mobility particle sizer, FMPS) plus light absorption and scattering at 870 nm (photoacoustic extinctiometer). For D p < 200 nm, the FMPS characterized sizing within ±20% compared to standards. As compared to the traditional scanning mobility particle sizer, the FMPS responded most accurately to single-mode polydispersions with mean D p < 200 nm, which characterized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 74 publications
4
31
2
Order By: Relevance
“…The lower temperature heat gun typically produced a size distribution shifted to larger sizes (geometric number mean diameter of 94 nm versus 30–34 nm for the hotter methods) as shown in Figure . The behavior is consistent with Carrico et al () and others who showed the influence on sizing of combustion characteristics with lower intensity smoldering combustion generally producing larger particles. Notably, this range of size distributions results in a coefficient of variation of 8% in f (RH) holding all else constant.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The lower temperature heat gun typically produced a size distribution shifted to larger sizes (geometric number mean diameter of 94 nm versus 30–34 nm for the hotter methods) as shown in Figure . The behavior is consistent with Carrico et al () and others who showed the influence on sizing of combustion characteristics with lower intensity smoldering combustion generally producing larger particles. Notably, this range of size distributions results in a coefficient of variation of 8% in f (RH) holding all else constant.…”
Section: Resultssupporting
confidence: 92%
“…Journal of Geophysical Research: Atmospheres Figure 9. The behavior is consistent with Carrico et al (2016) and others who showed the influence on sizing of combustion characteristics with lower intensity smoldering combustion generally producing larger particles. Notably, this range of size distributions results in a coefficient of variation of 8% in f(RH) holding all else constant.…”
Section: /2017jd028162supporting
confidence: 92%
“…The same trend is shown for number mean diameter. This is in contrast to Gomez et al (2018) and Carrico et al (2016), who show that the number mean diameter for the lower temperature method (heat gun) produced larger sizes when compared to the hotter ignition methods (lighter and resistance heater). This discrepancy can be partially explained by combustion conditions, that is, whether the burn was more flaming, smoldering, or a mixture of these two phases.…”
Section: /2018jd029892contrasting
confidence: 77%
“…Average mass mean diameter and average number mean diameter from SMPS measurements, average rBC mass concentration from SP2 measurements, and the emission ratio from each fire are presented. Studies such as Einfeld et al (1991), Woods et al (1991), Martins et al (1996), and Reid and Hobbs (1998) agree with Gomez et al (2018) and Carrico et al (2016) that larger particle sizes are present in low-temperature combustion conditions. Likewise, the ignition methods resulted in differing sizes.…”
Section: /2018jd029892mentioning
confidence: 82%
See 1 more Smart Citation